Thioredoxin-80 is a product of alpha-secretase cleavage that inhibits amyloid-beta aggregation and is decreased in Alzheimer's disease brain - Gil-Bea, Francisco (WILEY-VCH Verlag, 2012)
Thioredoxin-1 (Trx1) is an endogenous dithiol reductant and antioxidant that was shown to be decreased in Alzheimer's disease (AD) neurons. A truncated form of Trx1, thioredoxin 80 (Trx80), was reported to be secreted from monocytes having cytokine activity. Here, we show that Trx80 is present in human brain in an aggregated form. Trx80 localizes mainly to neurons and is dramatically decreased in AD brains. Trx80 levels in cerebrospinal fluid (CSF) correlate with those of the classical AD biomarkers amyloid-β (Aβ) 1–42 and total tau. Moreover, Trx80 measurements in CSF discriminate between patients with stable mild cognitive impairment, prodomal AD and mild AD. We report that ADAM10 and 17, two α-secretases processing the Aβ precursor protein, are responsible for Trx80 generation. In contrast to the periphery, Trx80 has no pro-inflammatory effects in glia, either by itself or in combination with Aβ or apolipoprotein E. Instead, Trx80 inhibits Aβ(1–42) aggregation and protects against its toxicity. Thus, a reduction in Trx80 production would result in increased Aβ polymerization and enhanced neuronal vulnerability. Our data suggest that a deficit in Trx80 could participate in AD pathogenesis.